Manajemen Produksi Siaran Berita Pojok Pantura Citra TV Selama Pandemi Covid-19 - Novelya Aleena Rofani; Ainur Rofiq (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2022)
Based on the background regarding the adaptation of broadcast media during the pandemic. The purpose of this research itself is to find out how the management of broadcast media production in this case Citra TV with the Pantura Corner program. The existence of social distancing regulations, of course, forces broadcast media to develop ways to continue to exist to present the latest and most accurate news. This research uses a case study method with data collection methods conducted through in-depth interviews, documents, archives, and several cases. Based on the results of the initial analysis in news coverage, journalists conducted direct interviews with sources. However, during the Covid-19 pandemic, interviews were conducted using a media conference (zoom) intermediary. If the coverage activities are destroyed in the green zone area, then the coverage is carried out directly while still complying with the protocols recommended by the government.